Volume-Based Thermodynamics: A Prescription for Its Application and Usage in Approximation and Prediction of Thermodynamic Data - Glasser, Leslie; Jenkins, H. D. (American Chemical Society, 2011)
Thermodynamics, as both thermochemistry and thermophysics, is fundamental and central to the science of matterand, in particular, of condensed materials. While extensive data resources for thermodynamic quantities do exist, none of theexperimental, simulation, or theoretical studies can keep pace with the rate of synthesis of new materials or provide reliable data forhypothesized materials. Correlation methods can fill this gap. We describe a range of recently developed correlation methods thatrely on volume to predict thermodynamic quantities. In parallel with these, thermodynamic difference rules, which describe howproperties of materials (say, of a group of solvates) may be inferred from corresponding properties of materials that neighbor them incomposition, have recently been reviewed.